PENGARUH SERVICE DELIVERY DAN SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN PADA PT.BFI FINANCE CABANG JAMBI - NOVITA EKASARI (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
Consumer financing is one of financial alternative that interest both public and enterpreneur to support their business life and will make the competition tightly. Financial company offers not only a competitive interest rate but also flexible regulation and good services to satisfy customers. Financial business is grouped in services business, so the product offered and how the product offered cannot be separated with good quality of services. These become company competitive advantage. Service offered can be measured with 5 indicators : customer involvement, time and place, image and responsibility of company. From these indicators, we can see weather performance indicators are good or bad. Service quality can be measured with 5 service quality dimensions : Tangible, emphaty, reliability, responsiveness, and assurance. From 5 dimensions, can be determined what dimension is good or bad. The purpose of this study is to investigate (1) performance and expectation on service quality offered to PT. BFI Finance’s customers, (2) Customer Loyalty at PT. BFI Finance, (3) How good is the service quality offered. The result of this research showed that service delivery and service qualitu variable have significant contribution on customer loyalty (67,63%). Meanwhile, partially service delivery also show a significant contribution on customer loyalty (28,39%) and service delivery contribution about (39,24%). The result mean that service delivery have more influence than service delivery on custo mer loyalty, and the influence of other factor about 32.37%. the result also showed that there are three level of customer loyalty at PT. BFI Finance Jambi: Repeat customer level (84.2%), client level (78.5%) and advocate level (72.8%).